Prognostic Immune-Related Genes of Patients With Ewing’s Sarcoma - Zhou, Yangfan; Xu, Bin; Wu, Shusheng; Liu, Yulian (Frontiers in Genetics, 2021)
Ewing's sarcoma (ES) is a highly aggressive malignant bone tumor with a high incidence among children and adolescents.So, we used ssGSEA to study the immune microenvironment in ES patients to find immune-related gene markers.In this study, ssGSEA was used to cluster the RNA-sequencing of 117 ES patients, and the immune cell infiltration of 117 ES patients downloaded from the target were evaluated, and high immune cell infiltration clusters, medium immune cell infiltration clusters and low immune cell infiltration clusters were obtained. Based on the comparison of clusters with high immune cell infiltration and low immune cell infiltration, normal skeletal muscle cells and ES, we found 198 common differentially expressed genes.GO and KEGG enrichment analysis show some the underlying immune mechanism is in ES.Then we use cox regression, and lasso regression to choose immune-related prognostic genes. An external data set from ICGC validated our results.10 immune-related prognostic genes were screened. They are "FMO2, GLCE, GPR64, IGFBP4, LOXHD1, PBK, SNAI2, SPP1, TAPT1-AS1, ZIC2" in the ES external validation group. The 10 immune-related prognostic genes also have high prognostic value. Univariate and multivariate Cox regression analysis showed that these 10 genes were independent prognostic factors.These 10 immune-related gene markers were determined to have independent prognostic significance for ES. The results of this study provide a means to predict the prognosis and survival of ES patients, and also provide a promising target for immunotherapy.